Use of bone-SPECT/CT and Na[18F]F-PET/CT in hyperparathyroidism - van der Bruggen, Wouter; Bulten, Bernard F. (Frontiers in Nuclear Medicine, 2025)
Hyperparathyroidism disrupts the balance of physiological bone formation and resorption by upregulating osteoclast activity. This leads to hypercalcemia, resulting in osteoporosis and eventually the formation of “brown tumors.” Currently used radiological and nuclear medicine imaging for primary hyperparathyroidism face challenges in accurately diagnosing bone-related complications. Molecular bone imaging techniques routinely consist of bone scintigraphy, with possible addition of bone-SPECT/CT. Recently, renewed interest has emerged in the use of Na[18F]F-PET/CT. Both applications are highly sensitive to in vivo osteoblast activity. However, the latter technique offers improved spatial resolution and sensitivity, as well as shorter incubation and faster scanning. This article summarizes current limitations and potential improvements in bone-SPECT/CT and Na[18F]F-PET/CT imaging in selected patients with hyperparathyroidism, compared to other relevant techniques and clinical parameters.